Evaluasi Pelaksanaan Kegiatan Penyelidikan Epidemiologi Dalam Program Pemberantasan Penyakit DBD Di Puskesmas Kampar - ega kartini; Kiswanto Kiswanto; Ahmad Hanafi; Yuyun Priwahyuni; Jasrida Yunita (Jurnal Kesehatan Komunitas, 2020)
ABSTRACT Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus and is a contagious disease that is still a public health problem in Indonesia. Kampar Regency is one of the regions that experienced an increase in DHF cases, especially in the Kampar Health Center area. Kampar Health Center has conducted DHF Epidemiology Investigation activities but the incidence of DHF is still increasing. The aim of the study was to evaluate the implementation of Epidemiological Investigations in the DHF Eradication Program in Kampar Health Center in 2018 as seen from the process indicators (collecting epidemiological data in accordance with PE form, checking mosquito larvae in a 100-meter landfill, as well as controlling the focus of dengue). This type of research is descriptive qualitative with the number of informants as many as 9 people. The results showed that the implementation of DHF PE in Kampar Health Center was still not effective, efficient, sufficient and appropriate because there was no clear SOP in each activity, absence of epidemiologists, lack of funding, lack of flow of DHF reporting, lack of public awareness in implementing PSN and the lack of socialization of the Puskesmas is related to the response of DHF, while in terms of equity and responsiveness it can be said both seen from the response time of PE implementation carried out no later than 1x24 hours after the reporting and implementation of activities without discriminating the social status of the community. It is recommended to the Puskesmas to complete all SOPs so that the implementers of the activities have a reference in their work and make a clearer PE implementation plan so that they can be implemented optimally so that the DHF problems can be overcome.